2017
DOI: 10.1038/s41598-017-11441-4
|View full text |Cite|
|
Sign up to set email alerts
|

Introduced ascidians harbor highly diverse and host-specific symbiotic microbial assemblages

Abstract: Many ascidian species have experienced worldwide introductions, exhibiting remarkable success in crossing geographic borders and adapting to local environmental conditions. To investigate the potential role of microbial symbionts in these introductions, we examined the microbial communities of three ascidian species common in North Carolina harbors. Replicate samples of the globally introduced species Distaplia bermudensis, Polyandrocarpa anguinea, and P. zorritensis (n = 5), and ambient seawater (n = 4), were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 80 publications
3
57
0
Order By: Relevance
“…Also, an extensive survey of 10 different ascidian microbiomes (representing both solitary and colonial forms) conducted on the Great Barrier Reef reported core memberships ranging from 2 to 35 OTUs (35), while the numbers of individuals surveyed in each case were only 2-3. Note that a few other studies reported much higher numbers of shared OTUs ranging from 93-238 (37, 38); the scale of sequencing was higher in these later studies.…”
Section: Discussionmentioning
confidence: 55%
“…Also, an extensive survey of 10 different ascidian microbiomes (representing both solitary and colonial forms) conducted on the Great Barrier Reef reported core memberships ranging from 2 to 35 OTUs (35), while the numbers of individuals surveyed in each case were only 2-3. Note that a few other studies reported much higher numbers of shared OTUs ranging from 93-238 (37, 38); the scale of sequencing was higher in these later studies.…”
Section: Discussionmentioning
confidence: 55%
“…However, variations in the relative abundance of these classes across the reefs were observed. Alphaproteobacteria have been shown to be major components of coral reef invertebrates lacking photosymbionts, such as particular sponges and ascidians (Bourne et al, ; Erwin, Pineda, Webster, Turon, & Lopez‐Legentil, ; Evans, Erwin, Shenkar, & López‐Legentil, ; Webster & Hill, ), while Rhodobacteraceae have been shown to be important components of marine biofilms (Dang & Lovell, ; Jones, Cottrell, Kirchman, & Dexter, ; Witt, Wild, Anthony, Diaz‐Pulido, & Uthicke, ). In contrast, Gammaproteobacteria, the second most abundant group in the current study, have been mainly associated with organisms harbouring photosynthetic symbionts (Bourne et al, ; Bourne & Munn, ; Cárdenas, Rodriguez‐R, Pizarro, Cadavid, & Arévalo‐Ferro, ; Hernandez‐Agreda et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, broadly introduced species face diverse temperature regimes, and microbial symbionts have been shown to play a role in adaptation of invertebrates to temperature changes (e.g., in corals: Ziegler et al, 2017;Osman et al, 2020). In this context, the tunic ascidian microbiome has been suggested to enhance to the adaptive capacity and invasion success of this group (Evans et al, 2017;Novak et al, 2017;Dror et al, 2019). Kott (2002) is an invasive colonial ascidian, native from the NW Pacific, with two main mitochondrial clades, named clade A and clade B, of which only clade A has spread in temperate seas worldwide (New Zealand, East and West coasts of North America, Atlantic and Mediterranean coasts of Europe, and South East of Russia: Lambert, 2009;Stefaniak et al, 2012;Ordóñez et al, 2015;Zvyagintsev et al, 2016).…”
Section: Introductionmentioning
confidence: 99%